Action Research: Pelaporan Insiden Keselamatan Pasien di IBS RSUP Dr. Soeradji Tirtonegoro Klaten - Sri Suparti (IJNP (Indonesian Journal of Nursing Practices), 2015)
Background: Reporting of patient safety incidents are the basis for building a system of patient care safer, more awareness in implementing patient safety reporting culture will require knowledge, awareness to change attitudes and behaviors become habits. Efforts to improve the knowledge, attitudes and behaviors with training demonstrations.Objective: The study is aimed to determine the risk of an incident, determine the level of knowledge, attitudes and behavior as well as provide recommendations to improve patient safety reporting culture in IBS RSST Klaten.Methods: action research, with purposive sampling, the population is nurses IBS RSST Klaten, validity triangulation, with content analysis. Results: Cycle I know the level of knowledge and ideology. Change of attitude: cognitive, all participants have no intention to make a report. Affective changes seen from the discussion/reflection, participants begin to understand these the type of incidents and how to create reports using the internal incident report form. Cycle II increased knowledge on the application and analysis, report formats charging 88.94 value. Change of attitude: cognitive, each participant had the courage to report the incident and presented 1, reporting the presence of behavioral change: of fi ve incident. Cycle III: The level of knowledge on the application, analysis and syntesis, charging value increased to 93.09 report format. Attitude: cognitive, aff ective, conative. According to the intensity at the level of respect and respondents reported (dare report all incidents). Changes in the number of reports the existence of 17 incidents. (22 reporting in 3 cycles). Data obtained KTD types of incidents: 7, KPC: 8, KNC: 4, and KTC: 3Conclusion: Action research with three cycles of training demonstrations, an increase in knowledge, change attitudes and behavior of all participants. There is a plan to followup and reporting of patient safety culture recommendations and unknown risk grading matrixs.Keywords: Cultural Reporting, Patient Safety, Demonstration Training